2012
DOI: 10.1021/ic300014a
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Diffusion of Oxygen through Ordered Carbon Vacancies in Zr2Cx: The Formation of Ordered Zr2CxOy

Abstract: Investigations are performed on low-temperature oxygen diffusion in the carbon vacancy ordered ZrC(0.6)and thus induced formation of the oxygen atom ordered ZrC(0.6)O(0.4). Theoretically, a superstructure of Zr(2)CO can be constructed via the complete substitution of carbon vacancies with O atoms in the Zr(2)C model. In the ordered ZrC(0.6), the consecutive arrangement of vacancies forms the vacancy channels along some zone axes in the C sublattice. Through these vacancy channels, the thermally activated oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…It is reasonable to expect that the high density of vacancies in the nitrogen-deficient particles makes them more susceptible to oxidation, with oxygen clearly diffusing within the core of the particles. This vacancy-induced oxidation mechanism has been reported for other refractory materials such as ZrC …”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…It is reasonable to expect that the high density of vacancies in the nitrogen-deficient particles makes them more susceptible to oxidation, with oxygen clearly diffusing within the core of the particles. This vacancy-induced oxidation mechanism has been reported for other refractory materials such as ZrC …”
Section: Resultssupporting
confidence: 73%
“…This vacancy-induced oxidation mechanism has been reported for other refractory materials such as ZrC. 48 Role of Oxidation on the Plasmonic Response. We have investigated the role of oxidation on the plasmonic response of TiN particles by monitoring the changes in their optical properties after annealing in air.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
“…It is also possible for carbon or oxygen to occupy the octahedral interstitial vacancies of the Zr lattice 20,21 . The oxycarbide was shown to exhibit the exact same rock salt structure of ZrC x (see the Powder Diffraction File, PDF, 035 0784 22 ) with similar 23 or smaller cell parameters 21 . Gendre et al 17 observed that oxycarbides with C/Zr ≥ 0.8, have the same XRD pattern as ZrC x while oxycarbides with C/Zr ≤ 0.7 could instead display some additional zirconia peaks 17 .…”
mentioning
confidence: 98%
“…The space group for both Zr 2 C and Zr 2 CO is Fd 3¯$\bar{3}$ m . The crystal structures of Zr 2 C and Zr 2 CO, which are shown in Figure 1, were built based on Rietveld refinement of X‐ray diffraction patterns 21 . First‐principles calculations were employed to optimize the crystal structures and to calculate the second‐order elastic constants.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…The crystal structures of Zr 2 C and Zr 2 CO, which are shown in Figure 1, were built based on Rietveld refinement of X-ray diffraction patterns. 21 First-principles calculations were employed to optimize the crystal structures and to calculate the second-order elastic constants. Phonon calculations were conducted with the finite displacement method.…”
Section: First-principles Calculations and Lattice Thermal Conductivitymentioning
confidence: 99%